2018
DOI: 10.3892/ijo.2018.4387
|View full text |Cite
|
Sign up to set email alerts
|

USP18 promotes breast cancer growth by upregulating EGFR and activating the AKT/Skp2 pathway

Abstract: Recent studies have suggested that ubiquitin-specific peptidase (USP)18 may act as an oncogene in various types of cancer. Although the role of USP18 in breast cancer cell lines has been elucidated, the underlying mechanisms and clinical role of USP18 in breast cancer are currently not well understood. The bioinformatics analysis and experimental results of the present study demonstrated that aberrant promoter methylation led to increased expression of USP18 in breast cancer. In addition, correlation analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 37 publications
2
33
0
Order By: Relevance
“…We observed that the decitabine treatment reduced the fraction of cells with prolonged delay times in USP18 induction, which is in part due to earlier USP18 upregulation ( Figure 5—figure supplement 4 ), supporting that the promoter methylation inhibits USP18 induction ( Figure 5D ). This result is consistent with a previous study showing that a decreased promoter methylation leads to increased USP18 expression in breast cancer ( Tan et al, 2018 ). We note that decitabine also leads to cell cycle arrest in G1 or G2 ( Shin et al, 2013 ; Lavelle et al, 2003 ).…”
Section: Resultssupporting
confidence: 94%
“…We observed that the decitabine treatment reduced the fraction of cells with prolonged delay times in USP18 induction, which is in part due to earlier USP18 upregulation ( Figure 5—figure supplement 4 ), supporting that the promoter methylation inhibits USP18 induction ( Figure 5D ). This result is consistent with a previous study showing that a decreased promoter methylation leads to increased USP18 expression in breast cancer ( Tan et al, 2018 ). We note that decitabine also leads to cell cycle arrest in G1 or G2 ( Shin et al, 2013 ; Lavelle et al, 2003 ).…”
Section: Resultssupporting
confidence: 94%
“…Further, knocking down USP18 suppresses cell growth and induces apoptosis in acute promyelocytic leukaemia [9]. Furthermore, USP18 promotes breast cancer growth by enhancing the activity of the AKT/Skp2 pathway [10]. However, USP's underlying role and signalling pathway in cervical cancer cells requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been confirmed that USP18 promotes breast cancer growth via improving the activity of AKT/Skp2 pathway. [10] However, the underlying role and signaling pathway of USP18 is less investigated in cervical cancer cells.…”
Section: Introductionmentioning
confidence: 99%